Intelligent Spaces The Application of Pervasive ICT - Steventon, Alan.; Wright, Steve; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2006)
Intelligent Spaces: The Application of Pervasive ICT sets out a vision where Information & Communication Technology (ICT) moves from the PC on the desktop out into the physical world, and becomes pervasive. The world about us will appear to have real intelligence embedded in it, creating what we term "Intelligent Spaces" or "iSpaces", which will augment and support virtually every human activity. An iSpace consists of • The physical world in which the user exists, in his/her relevant context. • The interface between the digital world and the physical world. This contains embedded sensors to gather data, labels to identify objects, actuators to control things/appliances in the physical world, together with support software to facilitate non-intrusive two-way communication across the interface, • The digital world in which digital knowledge and intelligent systems are available to intelligently analyse data gathered from the physical world, and to influence and support our actions in that physical world. Intelligent Spaces: The Application of Pervasive ICT describes the vision and how it has already been demonstrated in a number of applications ranging from the home, healthcare and traffic systems to monitoring glaciers. It identifies many of the technical, human and business issues which need to be researched before the benefits can become widespread, and describes possible solutions to them. Academic & industrial researchers in Computer Science, IT & Communications, as well as practitioners will find this key reading as it delivers practical & implementable current research.
Intelligent Spaces — The Vision,the Opportunities, and the Barriers -- The Socio-Economic Impact of Pervasive Computing — Intelligent Spaces and the Organisation of Business -- No Pervasive Computing Without Intelligent Systems -- The Supply Chain -- Care in the Community -- Pervasive Home Environments -- Traffimatics — Intelligent Co-operative Vehicle Highway Systems -- Mixed-Reality Applications in Urban Environments -- A Sensor Network for Glaciers -- Co-operation in the Digital Age — Engendering Trust in Electronic Environments -- Maintaining Privacy in Pervasive Computing — Enabling Acceptance of Sensor-based Services -- RFID Security and Privacy — Issues, Standards, and Solutions -- Ambient Technology — Now You See It, Now You Don’t -- Integrated Sensor Networks for Monitoring the Health and Well-Being of Vulnerable Individuals -- Segmentation and Tracking of Multiple Moving Objects for Intelligent Video Analysis -- An Attention-based Approach to Content-based Image Retrieval -- Eye Tracking as a New Interface for Image Retrieval -- The Implications of Pervasive Computing on Network Design -- Autonomic Computing for Pervasive ICT — A Whole-System Perspective -- Scale-Free Topology for Pervasive Networks -- NEXUS — Resilient Intelligent Middleware -- Intelligent Data Analysis for Detecting Behaviour Patterns in iSpaces -- xAssist — Inferring User Goals from Observed Actions -- Programming iSpaces — A Tale of Two Paradigms.
Keywords: Computers; Computer communication systems; Information Systems and Communication Service; Computer Communication Networks